Sneezing-Death Relationship: an Epigenetic Mutation: Sneezing-Death Relationship: an Epigenetic Mutation - Alabedi, Rihab F. (Scientific Journal of Medical Research, 2022)
There are many factors capable of inducing sneeze in some or all subjects as the presence of physical or chemical irritant in nasal mucosa, exposure to bright light, sexual ideation or orgasm, full stomach, and so on. The occurrence of sneezing in response to the presence of nasal mucosa irritant is considered as a normal protective mechanism to get rid from this irritant through the stimulation of the sneezing reflex, but, while reviewing articles related to this topic, we didn’t find any convincing scientific advantage for sneezing during exposure to other factors mentioned above. Add to that, except for few hypotheses, it is unknown that how these factors induce sneeze. We think that Imam Ja’afer Al-sadiq PBUH answered these questions about 1300 years ago using a very concise, scientifically rich, and highly connected talk. In this article we tried to explain this very common and not fully understandable phenomenon through a scientific analysis of Imam Ja’afer Al-Sadiq’s PBUH talk from a medical point of view.